Chemoenzymatic synthesis of 3-ethyl-2,5-dimethylpyrazine by L-threonine 3-dehydrogenase and 2-amino-3-ketobutyrate CoA ligase/L-threonine aldolase - Tomoharu Motoyama (Nature Portfolio, 2021)
Threonine is a biosynthetic precursor to dimethylpyrazine derivatives, but the pathway by which this occurs is not fully established. Here l-throenine-3-dehydrogenase and 2-amino-3-ketobutyrate CoA ligase together are shown to convert l-threonine to dimethylpyrazine derivatives as a byproduct of glycine metabolism.